2021
DOI: 10.1002/ajim.23285
|View full text |Cite
|
Sign up to set email alerts
|

PTSD symptoms, depressive symptoms, and subjective cognitive concerns in WTC‐exposed and non‐WTC‐exposed firefighters

Abstract: Background: Firefighting has been associated with posttraumatic stress disorder (PTSD) and other mental health conditions. We previously found that among Fire Department of the City of New York (FDNY) responders to the World Trade Center (WTC) disaster, higher-intensity WTC-exposure predicted PTSD symptoms, depressive symptoms, and subjective cognitive concerns. The present study aims to compare these symptoms in the FDNY WTC-exposed cohort versus a comparison cohort of non-FDNY, non-WTC-exposed firefighters. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 73 publications
(156 reference statements)
0
2
0
Order By: Relevance
“…Previous research has reported subjective cognitive concerns among WTC-exposed firefighters 4 . Yet, a large multicohort study found that WTC-exposed FDNY firefighters reported fewer cognitive concerns than firefighters from Chicago, Philadelphia, and San Francisco who were not exposed to the WTC attacks 5 , rendering unclear the clinical significance of self-reported cognitive concerns and correspondence to objectively measured deficits in cognitive function.…”
mentioning
confidence: 99%
“…Previous research has reported subjective cognitive concerns among WTC-exposed firefighters 4 . Yet, a large multicohort study found that WTC-exposed FDNY firefighters reported fewer cognitive concerns than firefighters from Chicago, Philadelphia, and San Francisco who were not exposed to the WTC attacks 5 , rendering unclear the clinical significance of self-reported cognitive concerns and correspondence to objectively measured deficits in cognitive function.…”
mentioning
confidence: 99%
“…The situation might be more salient in China, as depression has become the top 10 leading cause of all-cause disability-adjusted life years, possibly as the byproduct of the high-speed socioeconomic developments 5 . Noteworthy, compared with the general population, people with irregular work schedules 6 and heavy occupational stress, 7 such as physicians, 8 policemen, 9 and firefighters, 10 have a higher prevalence of depressive symptoms.…”
mentioning
confidence: 99%